The Potential Role of CDH1 as an Oncogene Combined With Related miRNAs and Their Diagnostic Value in Breast Cancer - Xie, Dan; Chen, Yiyu; Wan, Xue; Li, Jingyuan; Pei, Qin; Luo, Yanan; Liu, Jinbo; Ye, Ting (Frontiers in Endocrinology, 2022)
Background Breast cancer (BC) is the leading cause of cancer−related mortality in females and the most common malignancy with high morbidity worldwide. It is imperative to develop new biomarkers and therapeutic targets for early diagnosis and effective treatment in BC. Methods We revealed the oncogene function of cadherin 1 (CDH1) via bioinformatic analysis in BC. Moreover, miRNA database was utilized to predict miRNAs upstream of CDH1. Expression of CDH1-related miRNAs in BC and their values in BC stemness and prognosis were analyzed through TCGA‐BRCA datasets. In addition, Gene Ontology (GO) and Gene Set Enrichment Analysis (GSEA) were performed to explore the potential functions and signaling pathways of CDH1 in combination with CDH1-related miRNAs in BC progression. Finally, the differential expressions of soluble E-cadherin (sE-cad), which is formed by the secretion of CDH1-encoded E-cadherin into serum, analyzed by enzyme-linked immunosorbent assay (ELISA). Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) was used to detect the expression level of CDH1-related miRNAs in serum samples. Results The mRNA and protein expressions of CDH1 were elevated in BC tissues compared with normal counterparts. Moreover, CDH1 overexpression was positively correlated with BC stage, metastatic, stemness characteristics, and poor prognosis among patients. In predictive analysis, miR-340, miR-185, and miR-20a target CDH1 and are highly expressed in BC. miR-20a overexpression alone was strongly associated with high stemness characteristics and poor prognosis of BC. Additionally, GO, KEGG, and hallmark effect gene set analysis demonstrated that CDH1 in combination with overexpression of miR-340, miR-185, or miR-20a participated in multiple biological processes and underly signaling pathways involving in tumorigenesis and development of BC. Finally, we provide experimental evidence that the combined determination of serum sE-cad and miR-20a in BC has highly diagnostic efficiency. Conclusions This study provides evidence for CDH1 as an oncogene in BC and suggests that miR-20a may regulate the stemness characteristics of BC to exert a pro-oncogenic effect by regulating CDH1. Moreover, sE-cad and miR-20a in serum can both be used as valid noninvasive markers for BC diagnosis.